Does Internal Fund Create Trouble for Firms? The Effect of Investment and Dividend Policy toward Firm Value - Adi Kurniawan Yusup; Lydia Ari Widyarini; Charly Hongdiyanto (Master of Management, School of Business and Management, Petra Christian University, 2022)
Agency theory occurs when shareholders recruit a manager to manage the company. Both shareholders and managers tend to work in their best interests. The free cash flow hypothesis states that managers tend to use internal funds to invest in an unprofitable project rather than pay a dividend to shareholders. This research investigates whether internal fund available creates trouble (agency conflict) that can reduce the firm value in Indonesia's company by examining the relationship of operating cash flow as the source of internal funds to firm value through investment decision and dividend policy. The research object is the consumer non-cyclical sector listed on Indonesia Stock Exchange from 2015-to 2019. The purposive sampling technique selects forty-seven companies. Panel data was analyzed using two stages least square (2SLS). This research finds that operating cash flow positively affects firm value. Nonetheless, operating cash flow does not affect firm value through investment decisions and dividend policy in Indonesia.